PENGARUH PEMBERIAN MAKANAN TAMBAHAN ANAK SEKOLAH TERHADAP STATUS GIZI KADARHB DAN PRESTASI BELAJAR ANAK SD DI KOTA DENPASAR - I Putu Suiraoka; PP Sri Sugiani; IA. Eka Padmiari (SANGKAREANG, 2017)
Primary school-age children are an investment nation. The quality of the nation in the future is determined the quality of children today. Efforts to improve human resources must be done early, systematically and sustainably. The growth of primary school-age children is optimal depending on the intake of nutrients with good quality and quantity (Republika, 2010). The School Child Enhancement Program (PMT-AS) has a broad impact not only on the aspects of health, nutrition and education today but also directly affecting the quality of human resources in the future.The purpose of this study was to examine influence of additional School Feeding to the nutritional status, anaemia status, and learning achievement at Denpasar Municipality.This research is an quasi experimental research with One Group Pre-test design-Post-test Design. The research was conducted in two schools, SDN 12 Kesiman and SDN 8 Sanur, Denpasar City, in May-September 2016. The population in this study were all students who got PMT-AS in SD 12 Kesiman Kertalangu and SD 8 Sanur in Denpasar City. The sample size is determined based on the quota of each elementary school, 50 students who meet the inclusion criteria. Sample selection by simple random sampling. Independent variables studied are the number, type and frequency of PMT-AS delivery, the process of accompaniment is done while the dependent variable is Nutritional Status, hemoglobin level and learning achievement.Analysis of nutritional content of food PMT-AS distributed in schools obtained average calori value 161.62 (53.87% of 300 calories) and protein 4.11 (82.18% of 5 grams). The students nutritional status based on body mass index by age obtained : 33.5% overweight, 4.4% obese and 33.3% normal. The results of measurement of hemoglobin level of students before and after the PMT-AS program obtained prevalence of anemia before counseling 15% and after counseling 11%. Although there was a decrease in the prevalence rate of anemia but the decrease was not statistically significant. Judging from the learning achievement in the final semester based on report card, the minimum score of 60.9 and the maximum score of 91.5 with the average score 77.5+7.66